Dark‐Field Sensors based on Organometallic Halide Perovskite Microlasers. Issue 32 (26th June 2018) - Wang, Kaiyang; Li, Gang; Wang, Shuai; Liu, Shuai; Sun, Wenzhao; Huang, Can; Wang, Yujie; Song, Qinghai; Xiao, Shumin
Abstract: The detection of nanoscale objects is essential for homeland security, environmental monitoring, and early‐stage diagnostics. In the past few years, optical sensors have mostly been developed with passive devices such as microcavity and plasmonic nanostructures, which require external laser sources to operate and significantly increase the costs and bulks of sensing systems. To date, the potential of their active counterparts in optical sensors has not been well explored. Herein, a novel and robust mechanism to detect nanoscale objects with lead halide perovskite microlasers is demonstrated. Nanoparticles can be simply detected and sized by measuring the intensity of scattered laser light. In principle, the proposed concept is also applicable to electrically driven microlasers and it could find applications in portable point‐of‐care devices. Abstract : An organometallic halide perovskite microlaser is demonstrated as a dark‐field sensor to detect nanoscale objects. By measuring the intensity of the scattered laser light, nanoparticles can be simply detected and sized, making great strides for the practical application of perovskite microlasers.